European countries with a diagnosis of financial default: expectancy and fear of its announcement in Ukraine - Konchyn, V.I. (Економiчний часопис-XXI, 2011)
This paper reviews the economic situation of European countries that today are in deep external debt crisis and drew close to financial default, that can be announced by the foreign creditors and investors who can not for some reason get in time or on demand their money (the principal amount provided for use funds and (or) interest on them). However, in the article the situation of Ukraine’s foreign debt is considered, which significantly increased as a result of financial management of banks, business entities and due to government and central bank policies during the Orange epoch. The prospects for economic development in Ukraine are outlined in view of external debt problem after coming into power the command of the Party of Regions.